Gluing process for composite material blade containing metal covered edge

By treating the surface of the titanium alloy by pickling and anodizing, and treating the composite surface with atmospheric pressure and low temperature plasma, the problems of insufficient bonding strength and poor surface treatment process stability in the prior art are solved, and efficient bonding between titanium alloy and composite materials is achieved, which significantly improves the mechanical properties.

CN119589968APending Publication Date: 2025-03-11ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411565741.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the bonding strength of titanium alloy and composite materials is insufficient, and the process stability of traditional surface treatment methods is poor, which can easily cause environmental pollution and damage fibers, resulting in a decrease in strength.

Method used

Acid washing is used to remove the loose oxide film on the surface of the titanium alloy, anodize it to form a dense oxide film, and increase the surface roughness; the composite material is subjected to atmospheric pressure and low-temperature plasma treatment, and the active functional groups are introduced to improve the bonding interface strength with the adhesive film.

Benefits of technology

The bonding strength between titanium alloy and composite materials is significantly improved, and the mechanical properties are enhanced. After treatment, the overlap strength between carbon fiber composite and titanium alloy is increased by 68%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119589968A_ABST
    Figure CN119589968A_ABST
Patent Text Reader

Abstract

The invention discloses a bonding process for a composite material blade containing a metal covered edge, and relates to the field of bonding processes. The process comprises the following steps: putting a to-be-glued titanium alloy area into a mixed solution of nitric acid and hydrofluoric acid for full reaction, washing with water, and drying; using NaTESi as an electrolyte, using the treated titanium alloy as an anode, using a graphite electrode as a cathode, and carrying out an electrolytic reaction at normal temperature; performing atmospheric pressure low-temperature plasma treatment on the composite material; and the treated titanium alloy and the treated composite material are glued through a glue film. A loose oxidation film on the surface of the titanium alloy is removed through acid pickling, a compact oxidation film is formed on the surface of the titanium alloy through anodic oxidation, and the surface roughness is improved; the active functional groups and wettability of the surface of the composite material are increased through plasma treatment, and the bonding interface strength with the adhesive film is improved. The lap joint strength of the treated carbon fiber composite material and the titanium alloy is improved by 68% compared with that before treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bonding technology, and in particular to a bonding technology for composite blades containing metal edging. Background Art

[0002] Fan blades are one of the core components of aircraft engines, and the performance of aircraft engines is closely related to their development. As the aviation field places increasingly higher requirements on engine performance, studies have found that adding titanium alloy reinforcement edges to the leading edge of composite blades can improve the impact resistance of composite blades. Compared with mechanical connection methods, the adhesive bonding structure makes the stress distribution at the connection more uniform, while reducing weight and making parts more flexible, but the most important issue is the bonding strength of the bonding area. Therefore, the bonding technology of titanium alloy and composite materials is a crucial factor in the successful development of composite fan blades for aircraft engines.

[0003] Proper surface treatment is essential for achieving strong and durable bonding. Traditional titanium alloy surface treatment methods usually involve mechanical treatment to improve the surface properties of titanium alloys. However, such methods have poor process stability and have shortcomings such as causing environmental pollution. Manual grinding, sandblasting and other surface treatments on composite materials also have the above shortcomings and are prone to damage fibers, resulting in reduced strength.

[0004] Therefore, in view of the above shortcomings, the present invention provides a composite blade bonding process containing metal edging. The titanium alloy surface is anodized, and its process parameters are easy to control, which can significantly improve the chemical stability (corrosion resistance) and surface hardness of the titanium alloy. At the same time, it can generate a rough microstructure on the surface of the substrate, increase the roughness of the surface, and help to enhance the single lap strength. Plasma technology can cleanly and efficiently introduce active groups on the surface of the composite material, which is conducive to chemical cross-linking with the adhesive film and further improve the bonding strength. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a bonding process for composite blades with metal edging in view of the deficiencies in the prior art. The purpose is to remove the loose oxide film on the surface of the titanium alloy by pickling, form a dense oxide film on the surface of the titanium alloy by anodizing, and increase the surface roughness; increase the active functional groups and wettability of the composite surface by plasma treatment, and improve the bonding interface strength with the adhesive film. In this way, the mechanical properties of the composite blades with metal edging are improved.

[0006] The specific technical solutions adopted by the present invention are as follows:

[0007] The present invention provides a composite blade bonding process containing metal edging, which is as follows:

[0008] S1: Place the titanium alloy area to be bonded in a mixed solution of nitric acid and hydrofluoric acid for full reaction, rinse with water and dry;

[0009] S2: Using NaTESi as the electrolyte, the titanium alloy treated by S1 as the anode, and the graphite electrode as the cathode, the electrolysis reaction was carried out at room temperature;

[0010] S3: treating the composite material with atmospheric pressure low temperature plasma;

[0011] S4: The titanium alloy treated by S2 and the composite material treated by S3 are bonded by using an adhesive film.

[0012] Preferably, the titanium alloy is TC4 titanium alloy.

[0013] Preferably, in the mixed solution, the mass concentration of nitric acid is 65.0%-68.0%, the mass concentration of hydrofluoric acid is greater than or equal to 40.0%, and the volume ratio of nitric acid to hydrofluoric acid is 3:1.

[0014] Preferably, in S1, the reaction time of the titanium alloy and the mixed solution is 40 s, and the drying temperature is 60°C.

[0015] Preferably, the NaTESi solution comprises 300 g / L NaOH, 2 SiO 3 9H 2 O 14g / L, Na 2 C 4 H 4 O 6 ·2H 2 O 64g / L, EDTA 20g / L.

[0016] Preferably, in S2, the voltage of the electrolysis reaction is 10 V and the reaction time is 20 min.

[0017] Preferably, the process parameters of the atmospheric pressure low-temperature plasma treatment are: nozzle distance is 8 mm, equipment power is 800 w, and processing speed is 20 mm / s.

[0018] Preferably, the adhesive film is an epoxy adhesive film containing supporting fibers, and the curing agent in the adhesive film is a high temperature resistant aromatic amine type or catalytic type curing agent.

[0019] Furthermore, the supporting fiber is polyester fiber, polyamide fiber or glass fiber.

[0020] Preferably, the bonding is a process of curing in an autoclave according to the curing system of the adhesive film used.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The loose oxide film on the surface of the titanium alloy is removed by pickling process, and a dense oxide film is formed on the surface of the titanium alloy by anodizing process, which increases the surface roughness, increases the bonding area with the film, and enhances the mechanical interlocking effect of the interface; active functional groups such as alkoxy, carbonyl and carboxyl are introduced by plasma treatment to enhance the wettability and chemical crosslinking of the surface and improve the bonding strength with the film. By combining mechanical interlocking and chemical functionalization, the lap strength of the carbon fiber composite material and the titanium alloy after treatment is increased by 68% compared with that before treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a scanning electron microscope image of the titanium alloy surface before and after being treated by the process method of the present invention;

[0024] Figure 2 It is a contact angle change diagram of the titanium alloy surface before and after being treated by the process method of the present invention;

[0025] Figure 3 It is a strength deformation curve diagram of the adhesive joint of the titanium alloy and the composite material before and after the titanium alloy and the composite material are treated by the process method of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a composite blade bonding process containing metal edging, and the process method specifically comprises the following steps:

[0028] S1: First, the titanium alloy area to be bonded is placed in a mixed solution of nitric acid and hydrofluoric acid for sufficient reaction, and then the titanium alloy after the reaction is rinsed with water to remove excess solution and then dried.

[0029] As a preferred embodiment of the present invention, in this step, the titanium alloy used is TC4 titanium alloy, which belongs to the (a+β) type titanium alloy, has high specific strength and good comprehensive mechanical properties.

[0030] As a preferred embodiment of the present invention, in the mixed solution of nitric acid and hydrofluoric acid, the mass concentration of nitric acid is 65.0%-68.0%, the mass concentration of hydrofluoric acid is greater than or equal to 40.0%, and the volume ratio of nitric acid to hydrofluoric acid is 3:1.

[0031] As a preferred embodiment of the present invention, the reaction time between the titanium alloy and the mixed solution is 40 seconds. After being taken out, it is rinsed with deionized water and then placed in an oven at 60° C. for drying.

[0032] After the pickling operation in this step, the loose oxide film on the surface of the titanium alloy in the area to be bonded is removed.

[0033] S2: using NaTESi as the electrolyte, the titanium alloy treated in step S1 as the anode, and the graphite electrode as the cathode, and performing an electrolytic reaction at room temperature.

[0034] As a preferred embodiment of the present invention, in this step, the NaTESi solution used includes 300 g / L NaOH, 2 SiO 3 9H 2 O 14g / L, Na 2 C 4 H 4 O 6 ·2H 2 O 64g / L, EDTA 20g / L.

[0035] As a preferred embodiment of the present invention, in this step, the voltage of the electrolysis reaction is 10V and the reaction time is 20min.

[0036] After the operation of this step, a dense oxide film is formed on the surface of the titanium alloy after anodizing, which increases the surface roughness and improves the mechanical interlocking of the bonding.

[0037] S3: treating the composite material with atmospheric pressure low temperature plasma.

[0038] As a preferred embodiment of the present invention, the process parameters of atmospheric pressure low-temperature plasma treatment are: nozzle distance is 8mm, equipment power is 800w, and processing speed is 20mm / s.

[0039] After this step of treatment, the surface of the composite material acquires active functional groups such as alkoxy, carbonyl and carboxyl, which improve the surface energy, enhance the wettability of the surface to the adhesive film, and produce a chemical reaction with the adhesive film during the secondary bonding process, further improving the bonding strength.

[0040] S4: bonding the titanium alloy processed in the above step S2 and the composite material processed in the above step S3 by using an adhesive film.

[0041] Among them, the bonding is carried out in an autoclave according to the curing system of the adhesive film used, so as to tightly bond the treated titanium alloy and the composite material.

[0042] As a preferred embodiment of the present invention, the adhesive film is an epoxy adhesive film containing supporting fibers (common fiber types include polyester fibers, polyamide fibers and glass fibers), and the resin curing agent in the adhesive film can be a high temperature resistant aromatic amine type or catalytic curing agent.

[0043] The process and effects of the process of the present invention will be specifically described below through examples.

[0044] Example 1

[0045] This embodiment adopts the method of the present invention to perform surface treatment on titanium alloy and carbon fiber reinforced epoxy resin composite material and perform bonding strength test. The titanium alloy used is TC4 titanium alloy (Baoji Ronghe Titanium Metal Materials Co., Ltd.), the composite material prepreg is toughened high temperature curing epoxy resin prepreg (AVIC Composite Materials Co., Ltd.), and the adhesive film used is a modified epoxy film (AF191K, 3M). The specific treatment process is as follows:

[0046] First, immerse the bonding area of ​​the titanium alloy in a mixed solution of nitric acid and hydrofluoric acid (wherein the mass concentration of nitric acid is 65% and the mass concentration of hydrofluoric acid is 40%), and set the reaction time to 40 seconds to ensure that the surface of the bonding area of ​​the titanium alloy is fully wetted and clean. After the reaction, take out the titanium alloy and rinse it thoroughly with deionized water to remove the residual acidic solution. Subsequently, place the cleaned titanium alloy in an oven at 60°C to dry it to ensure that the surface is dry. The dried titanium alloy is used as the anode and electrolytically treated with NaTESi electrolyte. The ratio of NaTESi electrolyte is 300g / L NaOH, 2 SiO 3 9H 2 O 14g / L, Na 2 C 4 H 4 O 6 ·2H 2 O 64g / L, EDTA 20g / L. The graphite electrode was set as the cathode and 10V was applied at room temperature for 20 minutes to promote the formation of a dense oxide film on the surface of the titanium alloy. Figure 1 As shown in the figure, it can be seen that a dense oxide film is formed on the surface after treatment, a rough microstructure is generated, and the surface roughness is increased. Figure 2As shown in the figure, it can be seen that the contact angle decreases and the wettability improves after surface treatment. The composite material is treated with atmospheric pressure low-temperature plasma, and the processing parameters are: nozzle distance is 8mm, equipment power is 800w, and processing speed is 20mm / s. This treatment process can effectively improve the wettability of the composite surface and produce activated functional groups on the surface. Finally, the treated titanium alloy and the composite material are bonded with an adhesive film. Ensure that the adhesive film is evenly covered on the contact surface and cure at 177°C for 1h to form a composite blade bonding part with metal edging.

[0047] Example 2

[0048] This embodiment adopts the method of the present invention to perform surface treatment on titanium alloy and carbon fiber reinforced epoxy resin composite material and perform bonding strength test. The titanium alloy used is TC4 titanium alloy (Baoji Ronghe Titanium Metal Materials Co., Ltd.), the composite material prepreg is toughened high temperature curing epoxy resin prepreg (Y603, Zhongfu Shenying Carbon Fiber Co., Ltd.), and the adhesive film used is a modified epoxy film (AF191K, 3M). The specific treatment process is as follows:

[0049] First, immerse the bonding area of ​​the titanium alloy in a mixed solution of nitric acid and hydrofluoric acid (wherein the mass concentration of nitric acid is 68% and the mass concentration of hydrofluoric acid is 45%), and set the reaction time to 40 seconds to ensure that the surface of the bonding area of ​​the titanium alloy is fully wetted and clean. After the reaction, take out the titanium alloy and rinse it thoroughly with deionized water to remove the residual acidic solution. Subsequently, place the cleaned titanium alloy in an oven at 60°C to dry it to ensure that the surface is dry. The dried titanium alloy is used as the anode and electrolytically treated with NaTESi electrolyte. The ratio of NaTESi electrolyte is 300g / L NaOH, 2 SiO 3 9H 2 O 14g / L, Na 2 C 4 H 4 O 6 ·2H 2 O 64g / L, EDTA 20g / L. Set the graphite electrode as the cathode, and apply 10V of electricity at room temperature for 20 minutes to promote the formation of a dense oxide film on the surface of the titanium alloy. The composite material is treated with atmospheric pressure low-temperature plasma. The treatment process parameters are: nozzle distance 8mm, equipment power 800w, and treatment speed 20mm / s. This treatment process can effectively improve the wettability of the composite surface and produce activated functional groups on the surface. Finally, the treated titanium alloy and the composite material are bonded with an adhesive film. Make sure that the adhesive film is evenly covered on the contact surface and cure at 177°C for 1h. The lap strength is as follows. Figure 3 As shown in FIG. 1 , a composite blade bonded part with metal edging is finally formed. Figure 3 It can be seen that the single lap shear performance of the composite material after surface treatment of titanium alloy and composite material is improved by 68% compared with that of the untreated one.

[0050] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A composite blade bonding process containing metal edging, characterized in that: The details are as follows: S1: Place the titanium alloy area to be bonded in a mixed solution of nitric acid and hydrofluoric acid for full reaction, rinse with water and dry; S2: Using NaTESi as the electrolyte, the titanium alloy treated by S1 as the anode, and the graphite electrode as the cathode, the electrolysis reaction was carried out at room temperature; S3: treating the composite material with atmospheric pressure low temperature plasma; S4: The titanium alloy treated by S2 and the composite material treated by S3 are bonded by using an adhesive film.

2. A bonding process for composite blades with metal edging according to claim 1, characterized in that: The titanium alloy is TC4 titanium alloy.

3. The bonding process of composite blades with metal edging according to claim 1, characterized in that: In the mixed solution, the mass concentration of nitric acid is 65.0%-68.0%, the mass concentration of hydrofluoric acid is greater than or equal to 40.0%, and the volume ratio of nitric acid to hydrofluoric acid is 3:

1.

4. The bonding process of composite blades with metal edging according to claim 1, characterized in that: In S1, the reaction time of the titanium alloy and the mixed solution is 40 seconds, and the drying temperature is 60°C.

5. The bonding process of composite blades with metal edging according to claim 1, characterized in that: The NaTESi solution includes 300 g / L NaOH, 14 g / L Na2SiO3·9H2O, 64 g / L Na2C4H4O6·2H2O, and 20 g / L EDTA.

6. The bonding process of composite blades with metal edging according to claim 1, characterized in that: In S2, the voltage of the electrolysis reaction is 10V and the reaction time is 20min.

7. The bonding process of composite blades with metal edging according to claim 1, characterized in that: The process parameters of the atmospheric pressure low-temperature plasma treatment are: nozzle distance is 8 mm, equipment power is 800 w, and processing speed is 20 mm / s.

8. The bonding process of composite blades with metal edging according to claim 1, characterized in that: The adhesive film is an epoxy adhesive film containing supporting fibers, and the curing agent in the adhesive film is a high-temperature resistant aromatic amine type or catalytic type curing agent.

9. A bonding process for composite blades with metal edging according to claim 8, characterized in that: The supporting fibers are polyester fibers, polyamide fibers or glass fibers.

10. The bonding process of composite blades with metal edging according to claim 1, characterized in that: The bonding is a process of curing in an autoclave according to the curing system of the adhesive film used.

Citation Information

Patent Citations

  • Treatment method for titanium alloy covered edge of helicopter blade

    CN112846674A

  • Glue joint forming method for composite material fan blade and metal covered edge

    CN113459526A

  • Fiber metal laminated plate capable of improving interlaminar shear strength and weather resistance and preparation method of fiber metal laminated plate

    CN117507550A

  • Synergistic surface treatment method for improving bonding performance of carbon fiber composite material

    CN117621429A